2010
DOI: 10.3310/hta14460-04
|View full text |Cite
|
Sign up to set email alerts
|

Virus shedding and environmental deposition of novel A (H1N1) pandemic influenza virus: interim findings

Abstract: Declared competing interests of authors: JEE has received consultancy fees from GlaxoSmithKline and performed paid work for the Department of Health, England. KGN has received H5 avian influenza vaccines from Novartis and H1N1 pandemic influenza vaccines from GlaxoSmithKline and Baxter to facilitate MRC-and NIHR-funded trials. In addition, he has received consultancy fees from Novartis and GlaxoSmithKline and lecture fees from Baxter. A colleague of KGN at the University Hospitals of Leicester NHS Trust was pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 27 publications
(36 reference statements)
3
29
0
3
Order By: Relevance
“…Two randomized trials where influenza patients with naturally acquired infection were treated with oseltamivir no later than 36 hours after symptom onset also showed a significant reduction of severity, but differed in their assessment of the effect on viral shedding [33], [34]. Observational studies where requirements for oseltamivir treatment permitted treatment inception up to 48 hours after symptom onset often failed to demonstrate significant effects in viral shedding parameters [6], [28], [29] and our study is no exception in this regard.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…Two randomized trials where influenza patients with naturally acquired infection were treated with oseltamivir no later than 36 hours after symptom onset also showed a significant reduction of severity, but differed in their assessment of the effect on viral shedding [33], [34]. Observational studies where requirements for oseltamivir treatment permitted treatment inception up to 48 hours after symptom onset often failed to demonstrate significant effects in viral shedding parameters [6], [28], [29] and our study is no exception in this regard.…”
Section: Discussionmentioning
confidence: 48%
“…A few smaller studies on influenza (H1N1)pdm09 have also not been able to show significant age-dependent differences in the duration of viral shedding [28], [29], although others, both in seasonal [30] and pandemic influenza A(H1N1)pdm09 [31], have. The latter study was conducted among patients hospitalised with A(H1N1)pdm09 and demonstrated very clearly that duration of shedding is prolonged in hospitalised children <13 years [31].…”
Section: Discussionmentioning
confidence: 94%
“…In addition to RT‐PCR, five studies measured viral shedding by culture. Two studies measured viral shedding by culture for all study participants, and for 63% and 73% of patients in the other three studies. With the exception of one study in which median values were the same and the means differed by 0·3 day, the mean and median durations of viral shedding were 1·5–2 days shorter when measured by culture.…”
Section: Resultsmentioning
confidence: 99%
“…Influenza virus RNA has been detected in respirable airborne particles collected in healthcare facilities and other locations 9, 10, 11, 12, 13, 14, 15, 16. Influenza virus RNA also has been found in aerosol particles collected directly from infected patients while they were coughing and breathing 17, 18, 19, 20, 21, 22, 23. Six studies have demonstrated that influenza patients expel airborne particles containing viable virus 13, 18, 19, 21, 24, 25.…”
Section: Introductionmentioning
confidence: 99%